Could low adoption of modern maize varieties in Malawi be explained by farmers' interest in diverse seed characteristics? - Fisher, Monica; Mazunda, John (International Food Policy Research Institute, 2011)
Food security in Malawi depends on production of enough maize, the country's staple crop. In Malawi, more than 90 percent of farm households grow maize and this grain accounts for 60 percent of total calorie consumption. As opportunities for land-extensive agricultural growth are reduced, use of modern maize production technologies has become essential for producing sufficient maize to feed Malawi's people. Although the use of high-yielding modern maize seed is important for food security, some farmers are resisting complete adoption of these varieties. Understanding how farmer preferences and circumstances influence their decisions to adopt or increase the use of modern maize seed varieties is necessary. Otherwise, researchers may not develop appropriate technologies and policymakers may not design and execute the most effective policies for promoting improved varieties and technologies. This policy brief draws on key findings from a recent study by Lunduka, Fisher, and Snapp (2011) in which factors that influence the decisions of Malawian smallholder farmers to grow modern maize varieties were examined.